2019
DOI: 10.3390/su11174567
|View full text |Cite
|
Sign up to set email alerts
|

Control Strategy Optimization for Two-Lane Highway Lane-Closure Work Zones

Abstract: Traffic control is very important for two-lane highway lane-closure work zone traffic management. Control of the open lane’s right of way is very similar to that of a two-phase signalized intersection. Thus, four control strategies including flagger control, pre-timed control proposed by Schonfeld, pre-timed control proposed by Webster, and actuated control are employed for possible use at work zones. Two primary methodologies, the mathematical delay model adopted from signalized intersections, and the simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…On the other hand, for two‐lane highways, the model considers a speed reduction of 55% for slight and moderate damage according to the values empirically observed by Hua et al. (2019) in work zones on these types of highways. The model considers a 100% speed reduction for severe damage.…”
Section: Risk Model Application In Central Chilementioning
confidence: 99%
“…On the other hand, for two‐lane highways, the model considers a speed reduction of 55% for slight and moderate damage according to the values empirically observed by Hua et al. (2019) in work zones on these types of highways. The model considers a 100% speed reduction for severe damage.…”
Section: Risk Model Application In Central Chilementioning
confidence: 99%
“…The average intersection travel times based on the field data and simulation were compared to validate the accuracy of the calibrated VISSIM model. The percentage error (PE) was used to measure the difference between the observed and simulated travel times [44]. By defining TT S and TT R as the measured travel time from simulation and reality, respectively, the PE can be obtained following Equation (16).…”
Section: Vissim Model Calibrationmentioning
confidence: 99%
“…Among the studies related to two-lane segments, different approaches were found for evaluating traf ic performance in interventions of this type, such as deterministic (Cassidy and Han, 1993) or stochastic (Son, 1999) and microscopic simulations (Shibuya et al, 1996;Washburn et al, 2008;Zhu et al, 2017;Hua et al, 2019). However, the literature still lacks a more comprehensive exploratory analysis that incorporates the speci icities inherent to the problem and thus a suitable method to predict the impacts of the intervention under various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have applied traf ic simulation techniques (Shibuya et al, 1996;Washburn et al, 2008) to incorporate regression models to determine the delay time as a function of a series of input parameters, such as traf ic low, percentage of heavy vehicles, and work zone length. The studies by Zhu et al (2017) and Hua et al (2019) compared the performances of stop-andgo operations adopting ixed and dynamic green intervals. Both studies concluded that the best strategy is to maintain the traf ic low released in each direction only during the queue dissipation state.…”
Section: Introductionmentioning
confidence: 99%